Hurricane Hazard Assessment Along the United States Northeastern Coast: Surface Wind and Rain Fields Under Changing Climate - Snaiki, Reda; Wu, Teng (Frontiers in Built Environment, 2020)
Surface wind and rain fields are two significant elements of hurricane-induced hazards in coastal areas. Mitigation of losses due to hurricane wind and rain hazards has become an increasing urgent and challenging issue in light of changing climate and continued escalation of coastal population density, prompting the need for a more advanced risk analysis methodology to take global warming effects into consideration. In this study, the assessment of hurricane surface wind and rain hazards under changing climate is achieved by performing three simulation components, namely an enhanced hurricane track model to generate the synthesized storms (including a physics-based intensity model integrating sea surface temperature (SST), wind shear, and convective instability contributions), a newly developed thermal wind balance-based model to simulate the gradient wind profiles (explicitly considering environmental conditions of SST, temperature at the top of atmospheric boundary layer, and outflow temperature), and a height-resolving boundary-layer model to obtain the surface wind and rain fields (reducing inherent uncertainties associated with conventionally used gradient-to-surface wind speed conversion factors). A total of 10,000 years of hurricane events are generated for both observed (historical) and projected climate conditions, and a systematical comparison between these two scenarios is investigated. The simulation and comparison results highlight the important effects of a global warming scenario on hurricane surface wind and rain fields, and hence on critical civil infrastructure in hurricane-prone areas.